Pengaruh lklan Terhadap Perilaku Konsumerisme - Rahayu, lin Tri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2005)
This research tried to find a description about the influence of advertisement to consumerism behavior, factors that influencing in decision to buy and medias of advertisement in which giving bigger influence in decision to buy. This research was conducted in Malang. The method research used is qualitative method Method which used in data collecting is interview. The interview method used was complimentary leaded method. The result of this research are (1) advertisement influencing consumerism attitude and consumerism behavior, (2) factors that influencing the decision to buy for example requirement at that moment, quality of products, benefit an product and influence of others (friend, family member and others) (3) most utilized effective media to display advertisment products are television and then magazine, newspaper, radio and which at least having an effect on is pamphlets.